Downside Risk Implications of Multinationality and International Joint Ventures - Reuer, Jeffrey J.; Leiblein, Michael J. (Academy of Management Journal, 2000)
Investments in dispersed foreign subsidiaries and international joint ventures (IJVs) are often thought to enhance corporate flexibility and thereby reduce risk. The authors tested these predictions from real options theory and the international strategy literature using a set of recently developed downside risk measures. The evidence reveals that U.S. manufacturing firms with greater multinationality or investment in IJVs do not generally obtain lower levels of downside risk. Implications for theory and future empirical research are offered.